The Existence of Crocodile Bread at the Betawi Community Wedding’s Offerings in Christian Education Perspective - Liauw Fidelia Lesmana; Demsy Jura (GoAcademica Research & Publishing, 2022)
The use of crocodile bread is very important as part of the offerings at the Betawi traditional wedding ceremony. The 'Seserahan' event is a series that must exist at the wedding where the groom is the giver of material to the bride with a symbolic meaning. In general, the Betawi people believe that the crocodile is an animal with a symbol of loyalty. This article attempts to describe the existence of crocodile bread in a series of 'Seserahan' at Betawi weddings. Crocodile bread is seen as a symbol of the loyalty of the two parties who agreed to build a household and this principle is believed to this day. The study of the existence of crocodile bread in the Betawi people's wedding ceremony, which is viewed from the perspective of Christian education, is expected to provide enlightenment for those who want to observe this local wisdom so that they can add cultural insight. By using a descriptive approach, it is hoped that this study will provide the information needed when discussing the existence of this crocodile bread. Christian education conveys educative information so that people can understand the existence of crocodile bread responsibly based on Christian values.